2002
DOI: 10.1046/j.1365-2699.2002.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Oak, chestnut and fire: climatic and cultural controls of long‐term forest dynamics in New England, USA

Abstract: Aim Despite decades of study we have limited insights into the nature of the pre-European landscape of the north-eastern USA and the forces and changes that shaped modern forest patterns. Information on such long-term forest dynamics would provide critical insights into the relationships among environmental change, land-use history and biotic responses and is greatly needed for conservation planning. To address these issues we used modern, historical, and palaeoecological approaches to reconstruct the 3500year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 93 publications
(182 reference statements)
0
57
1
1
Order By: Relevance
“…It was hypothesized that periodic, low intensity surface fires were necessary for the development and maintenance of oak forests during the pre-settlement era (Abrams, 1992;Lorimer, 2001;Brose et al, 2001). Analysis of fossilized charcoal from lake sediments supports the assertion that fires were common in some oak dominated areas during the pre-settlement era Parshall and Foster, 2002;Foster et al, 2002), although not all oak forests contained abundant charcoal . The few studies of fire scars from old-growth oak forests in eastern oak forests also showed frequent fires in the pre-settlement era, with estimated fire return intervals of 4-20 years (Buell et al, 1954;Dey and Guyette, 2000;Shumway et al, 2001).…”
Section: Introductionmentioning
confidence: 71%
“…It was hypothesized that periodic, low intensity surface fires were necessary for the development and maintenance of oak forests during the pre-settlement era (Abrams, 1992;Lorimer, 2001;Brose et al, 2001). Analysis of fossilized charcoal from lake sediments supports the assertion that fires were common in some oak dominated areas during the pre-settlement era Parshall and Foster, 2002;Foster et al, 2002), although not all oak forests contained abundant charcoal . The few studies of fire scars from old-growth oak forests in eastern oak forests also showed frequent fires in the pre-settlement era, with estimated fire return intervals of 4-20 years (Buell et al, 1954;Dey and Guyette, 2000;Shumway et al, 2001).…”
Section: Introductionmentioning
confidence: 71%
“…Both mockernut hickory and white oak allocated <35% to the aboveground, which is believed to allow them to survive better under a frequent top-kill due to surface fire as well as on dry sites or during drought periods (e.g., Johnson et al, 2002). It appears that American chestnut adopts a life history strategy similar to tulip poplar and red maple, despite that fire has been attributed to its pre-blight dominance (Foster et al, 2002). The role of fire in regenerating American chestnut needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The timing is not consistently synchronous in these records, but this period is characterized in general by relatively large shifts in both temperature and moisture. Such oscillations alone may help explain a sharp rise in chestnut and hemlock in the Northeast coupled with a large increase in charcoal influx in some areas around the same time (Foster et al, 2002;Parshall et al, 2003). Similarly large climate shifts are observed in both the temperature and hydroclimate records during the MCA, particularly around 1000 CE, and throughout the LIA.…”
Section: Reconstructed Hydroclimate Variations In the Ne Us For The Lmentioning
confidence: 99%